Evaluasi Rasionalitas dan Efektifitas Penggunaan Antibiotik pada Pasien Pneumonia Pediatrik di Instalasi Rawat Inap Rumah Sakit Pusat Jawa Tengah - Bestari, Mahardika Putri; Karuniawati, Hidayah (Pharmacon: Jurnal Farmasi Indonesia, 2017)
Pneumonia is a respiratory infections disease are caused by bacterial, viral, fungal and parasitic pathogens that cause deaths in children, especially toddlers and increasing number incidents per year. Treatment of pneumonia treated with antibiotics rational and effective because can improve clinical therapeutic effects, minimize drug toxicity, reduce the incidence of resistance that leads to treatment failure, and more economically. The purpose of this study are to determine the rationale and effectiveness of antibiotic therapy. This study was an observational study with retrospective data retrieval using medical record data of pediatric patients diagnosed pneumonia in center hospital, Central Java. The results of 90 cases studied were 60% of patients treated with single antibiotics and 40% of patients treated with combination antibiotics. The most antibiotics given in single therapy were ampicillin (22,2%), amoxicillin (16,7%), and ceftriaxone (15,6%). While antibiotics in combination therapy was ampicillin with gentamicin 31.2%. rationality result analysis was: right indication 100%; proper patients 100%; appropriate medicines 72,2%; appropriate dose 9,23% and rational antibiotics 6,67%. Giving antibiotics ampicillin with gentamycin effective in eradicating bacteria this could be seen with temperature and leukocyte rate down, antibiotics did not improve on symptoms of patients.